Analisis Kemampuan Pemahaman Konsep Matematis Siswa SMP Pada Materi Relasi dan Fungsi Berdasarkan Teori Honey Mumford - Andaru Retno Kuncoro; Redo Martila Ruli (Jurnal Ilmiah Dikdaya, 2022)
The purpose of this study was to describe the understanding of mathematical concepts of junior high school students on Relation and Functions based on Honey Mumford Theory. The research uses a descriptive qualitative approach and the type of research used is a case study. In this study, there were 24 respondents, then 8 students were selected, representing 2 students from each learning style. The data collection method in this study was a learning style questionnaire LSQ (Learning Style Questionnaire) according to Honey Mumford, written tests and interviews. This study uses reduction, data presentation, and drawing conclusions into data analysis techniques. The results showed that: 1) Students with an activist learning style when studying tended to like new things so they were less careful with indicators that restated a concept, and did not like activities that took a long time which caused errors in calculating number operations. 2) Reflector learning style students at the time of learning are quite careful and calculating so that they are able to classify objects according to certain properties, but tend to focus on sources of information so that they are not able to present concepts in various forms of mathematical representation and apply concepts to problem solving. 3) Students with theoretical learning styles when learning many considerations and everything depends on theory so they are able to classify objects according to certain properties, but have not been able to present concepts in various forms of mathematical representation. 4) Students with pragmatic learning styles will study the material in detail so that they can restate a concept, but pragmatic students are too centered on sources of information which causes students not to be able to apply concepts or algorithms in problem solving. The conclusion of this study states that each student's learning style will lead to a different understanding of mathematical concepts.